Antioxidant Potential Profile of Extracts from Different Parts of Stem of Eucalyptus camaldulensis - Qureshi, M.Z.; Bashir, T.; Khurshid, S.; Akhtar, N.; Rehman, T.; Hussain, G.; Rahman, J.; Khan, M.A. (Asian Journal of Chemistry, 2012)
Eucalyptus camaldulensis is a powerful antiseptic and is used for relieving coughs, cold, sore throats and other infections. It is conventionally used against deteriorating diseases so it is an important task to gauge their antioxidant activity. Antioxidant potential and radical scavenging activity of the five fractions were examined by using different antioxidant assays such as ferric reducing antioxidant power, ABTS 2,2´-azinobis(3-ethylbenzothiazoline-6-sulphonic acid), total phenolic contents and DPPH (diphenyl-1-picrylhydrazyl radical) radical scavenging assay. Trolox equivalent antioxidant activity (TEAC) of the aqueous and organic fraction of these herbs was determined by calculating the per cent inhibition of the coloured radical solution after reaction with sample and standard antioxidants by comparing with the standard curve formed by Trolox as standard antioxidant. Total phenolic contents and ferric reducing antioxidant power decolourization assays of bark, sapwood heartwood of Eucalyptus camaldulensis showed a broad range of antioxidant activity. The results of such anti disease activities of the herb can be attributed to antioxidant compounds, which may be present in the plant under study.